Developing leadership through cooperative learning - Fernando, Baby Bernadette Mariano (2006)
The study measured the effectiveness of cooperative learning approach (CLA) in the development of leadership skills. Experimental approach was used having a pretest and post test control group design. A 5-day training was conducted using two different approaches: traditional and cooperative learning approach. 43 participants underwent the training. The study proved that cooperative learning approach develops leadership skills better than the traditional approach. A slight relationship was determined when the relationship between participants' profile and leadership skills development was analyzed.